2014
DOI: 10.1007/s10620-014-3277-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Serrated Polyps of the Colorectum

Abstract: Serrated pathway polyps are a relatively new area of interest in the field of colorectal cancer screening and prevention. Akin to conventional adenomas, some serrated polyps (SPs) have the potential to develop into malignant serrated neoplasms, yet little is known regarding risk factors for these lesions. Early epidemiological studies of hyperplastic polyps (HPs) were performed without knowledge of the serrated pathway, and likely included a mixture of SPs. More recently, studies have specifically evaluated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 81 publications
3
43
0
Order By: Relevance
“…Lifestyle and dietary risk factors are the most common risk factors for development of HP according to epidemiological studies; other risk factors include alcohol consumption, cigarette smoking, obesity, metabolic syndrome, and fiber intake [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle and dietary risk factors are the most common risk factors for development of HP according to epidemiological studies; other risk factors include alcohol consumption, cigarette smoking, obesity, metabolic syndrome, and fiber intake [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for adenomas and serrated polyps might differ between men and women and could be important when flexible sigmoidoscopy is considered as a screening tool. 27 Being male is a well established risk factor for adenomas, but the evidence for sex as a risk factor for SSA/P is limited and conflicting. [28][29][30] Some reports have found that being female is an independent risk factor for SSA/P, but others have not confirmed this finding.…”
Section: Principal Findingsmentioning
confidence: 99%
“…The role of various modifiable and lifestyle risk factors have been described for colorectal pathologies, most notably for colorectal adenomas [17][18][19][20][21] . To date, only alcohol has been evaluated systematically with regards to SP risk and it was found that moderate and heavy alcohol intake significantly increased SP risk, by 19% and 60%, respectively 22 .…”
Section: Introductionmentioning
confidence: 99%